Chitosan isolated from horseshoe crab tachypleus gigas from the Malay Peninsula - Kassim, Zaleha; Wan Murni, Wan Nurul Akmal; Md Razak, Mohd Razali; Wan Omar, Wan Sayzzawani; Adam, Sakinah Begum (Oriental Scientific Publishing Company, 2018)
Chitosan that was isolated from horseshoe crabs, Tachypleus gigas, for this study were from estuary area in Balok Pahang (East coast) and Muar Johor (West coast) of the Malay Peninsula. The isolation of chitosan was carried out by chemical processes involving deproteinization, demineralization and deacetylation. Physicochemical properties and antibacterial activity were analysed to determine its potential commercialization. The degree of deacetylation (DD) was higher for samples from Balok than Muar (42.4% and 35.2% respectively), but lesser than the commercial grade. There was no significant difference (p>0.05) in the physicochemical properties but obviously they had lesser moist (1.11±0.22 - 1.25±0.13%), higher ash content (1.99±0.06 - 2.37±0.07%), and low in its solubility (58.00±9.63 - 61.70±1.35%) as well as viscosity (52.52±5.38 - 64.37±4.73 cP) if compared with commercial chitosan. Chitosan from both field sites also showed great antibacterial activities which concentration dependent against Staphylococcus aureus and Eschericia coli.